The Relationship Between Gender and WASH Development Projects in Rural Uganda - Smyrilli Christiana; McRobie Allan (Journal of Management Practices, Humanities and Social Sciences, 2017)
The paper aims to explore the relationship between gender roles and development infrastructure projects in the Water, Sanitation, and Hygiene (WASH) sector in rural Uganda. It focuses on the influence of various factors including education and governance. Insights into developing infrastructure that addresses the needs of communities could emerge from understanding the multiple dimensions of the intrinsic and extrinsic factors that affect the roles that men and women play within the WASH sector. This study adopted a qualitative approach. Fieldwork has been undertaken in a number of rural communities in south Uganda, where group discussions and interviews were conducted with key players in the WASH sector, government representatives, and people from the communities. The collected data provided an understanding of how gender roles are influenced by other factors, as they are dependent on, and formed by, other social structures, and consequently how this relationship influences the infrastructure. The findings highlight the importance of good leadership by both men and women at community level, which leads to improvements in WASH infrastructure provision. Moreover, there seems to be a strong relationship between educating women and improved sanitation and hygiene practices. Finally, cultural attributes seem to have a strong influence on the way men and women view water and sanitation tasks, how they perform them, and how they engage with and value the infrastructure. The paper gives an overview of the findings and suggests future research which can lead to new evidence to support gender-sensitive infrastructure.